The Effect of Motivation and Work Discipline on Employee Performance at PT. Simponi Sigmanera - Valenzchi Yufancua; Cecep Haryoto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of work motivation and work discipline on employee performance at PT. Simponi Sigmanera, with motivation and work discipline as independent variables and employee performance as the dependent variable. The research used a quantitative associative method with primary data collected from the population of all permanent employees and a random sample of 60 respondents. The results show that work motivation has a significant effect on employee performance, with a t-value of 2.696 greater than the t-table value of 1.671 (2.696 > 1.671) and a significance value of 0.034 < 0.05. Work discipline also has a positive and significant effect on employee performance, with a t-value of 5.007 greater than the t-table value of 1.671 (5.007 > 1.671) and a significance value of 0.000 < 0.05. Collectively, work motivation and discipline significantly influence employee performance at PT. Simponi Sigmanera, demonstrating the importance of these variables in improving performance.